Cytotoxic Activity of Ethyl-para-methoxycinnamate from Kaempferia galanga L. on A549 Lung Cancer and B16 Melanoma Cancer Cells - Riza Apriani; Fajar Fauzi Abdullah (Jurnal Kimia Sains dan Aplikasi, 2021)
Kaempferia galanga L. belongs to the family of Zingiberaceae, an endangered medicinal plant with pharmacology activities. Ethyl-p-methoxycinnamate (EPMC) is an essential phytoconstituent of K. galanga rhizomes. Several studies have reported that EPMC has anticancer activities in several cancer cells, including CL-6 gallbladder cancer cells, HepG2liver cancer cells, MCF-7 breast cancer cells, and Raji lymphoma cancer cells. However, studies on A549 lung cancer and B16 melanoma cancer cells have not been reported. This study aimed to determine the anticancer activity of EPMC against A549 lung cancer and B16 melanoma cancer cells. EPMC was obtained by extraction using n-hexane, then recrystallized with chloroform. The isolate was then analyzed by thin-layer chromatography (TLC), and the structure was characterized by Fourier Transform Infrared (FTIR) and Nuclear Magnetic Resonance (NMR) spectroscopy. Cytotoxic activity was determined under Presto Blue assay. Based on the result, EPMC from K. galanga showed the cytotoxic effect on B16 cells with an IC50 value of 97.09 μg/mL, whereas EPMC showed no significant cytotoxic effect on A549 with an IC50 value of 1407.75 μg/mL. It was concluded that EPMC has potential cytotoxic on B16 melanoma cancer cells, but it showed inactive activity against A549 lung cancer cells. Further molecular mechanism underlying EPMC cytotoxic activity needs to be conducted.